2010
DOI: 10.1111/j.1399-3038.2010.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors for the persistence of cow’s milk allergy

Abstract: Cow's milk allergy (CMA) is usually transient, but recent studies have shown a later acquisition of tolerance to CM. Our aims were to characterize a population of Portuguese children with CMA and to identify predictive factors for the persistence of this food allergy. Children with CMA observed in our Paediatric Allergy Clinic between 1997 and 2006 were selected. Demographic and clinical data were collected from medical records. The group of children who tolerated CM before the age of 2 was compared with the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
97
1
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 28 publications
8
97
1
11
Order By: Relevance
“…Presence of anaphylaxis was the only clinical aspect that showed significant differences between persistent and tolerant groups (Table 1), as previously shown in the same service by Jacob et al 2 Atopic dermatitis had no significant influence on this difference, as described by Payot et al 13 Factors previously described such as asthma and allergies to other foods were identified as independent predictors for persistent CMPA after the age of 2 years, 14 not observed in the present study.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Presence of anaphylaxis was the only clinical aspect that showed significant differences between persistent and tolerant groups (Table 1), as previously shown in the same service by Jacob et al 2 Atopic dermatitis had no significant influence on this difference, as described by Payot et al 13 Factors previously described such as asthma and allergies to other foods were identified as independent predictors for persistent CMPA after the age of 2 years, 14 not observed in the present study.…”
Section: Discussionsupporting
confidence: 81%
“…Jacob et al, 2 in 2010, evaluating patients with CMPA from the same service, identified that 45% of the individuals were tolerant by the age of 5 years; in our sample, we found that the rate of resolution in the same age range fell to 37.9%. In 2010, Santos et al 14 found tolerance in only 22% of the children aged up to 5 years. Skripak et al, 1 in 2007, found that 21% of the children with CMPA persisted allergic up to the age of 16 years.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study by Martorell et al, which examined 170 infants diagnosed with milk allergy, the authors indicate persistent milk allergy at different ages between 12 and 48 months, which vary considerably from person to person [10]. Additionally the study of Santos et al, also indicated that the larger the value of sIgE, less the likelihood of an individual for developing tolerance [11], and The Sek et al reported that a decrease of about 50 % or 90 % of the values sIgE within a 12 month period associated with a probability of achieving tolerance to 0.31 and 0.66, respectively [12].…”
Section: Discussionmentioning
confidence: 97%
“…In a prospective study by Martorell et al, which examined 170 infants diagnosed with milk allergy, the authors indicate persistent milk allergy at different ages between 12 and 48 months, which vary considerably from person to person [10]. Additionally the study of Santos et al, also indicated that the larger the value of sIgE, less the likelihood of an individual for developing tolerance [11], and The Sek et al reported that a decrease of about 50 % or 90 % of the values sIgE within a 12 month period associated with a probability of achieving tolerance to 0.31 and 0.66, respectively [12].It is therefore assumed that most clinical features of generalized atopic reaction are non -specific, as the clinical and serological data can be seen in many infectious diseases and diseases with hereditary characteristics. Also if and allergic skin reaction may be second in frequency after gastrointestinal disorders, the extent of the allergic reaction and the intensity of symptoms throughout the body of the infant was examined in this study, combined with poor health conditions, make diagnosis and rapid treatment imperative.…”
mentioning
confidence: 97%
“…1 Dos doentes com APLV, até 50% desenvolvem alergias a outros alimentos, 9,10 até 40% apresentam asma, 20% eczema atópico e até 30% rinoconjuntivite. 9 No presente caso clínico, a doente tinha história de eczema atópico e asma.…”
Section: Discussionunclassified